Non-Fullerene Polymer Solar Cells Based on Alkylthio and Fluorine Substituted 2D-Conjugated Polymers Reach 9.5% Efficiency - Bin, Haijun; Zhang, Zhi-Guo; Gao, Liang; Chen, Shanshan; Zhong, Lian; Xue, Lingwei; Yang, Changduk; Li, Yongfang (Journal of the American Chemical Society, 2016)
Non-fullerene polymer solar cells (PSCs) with solution-processable n-type organic semiconductor (n-OS) as acceptor have seen rapid progress recently owing to the synthesis of new low bandgap n-OS, such as ITIC. To further increase power conversion efficiency (PCE) of the devices, it is of a great challenge to develop suitable polymer donor material that matches well with the low bandgap n-OS acceptors thus providing complementary absorption and nanoscaled blend morphology, as well as suppressed recombination and minimized energy loss. To address this challenge, we synthesized three medium bandgap 2D-conjugated bithienyl-benzodithiophene-alt-fluorobenzotriazole copolymers J52, J60, and J61 for the application as donor in the PSCs with low bandgap n-OS ITIC as acceptor. The three polymers were designed with branched alkyl (J52), branched alkylthio (J60), and linear alkylthio (J61) substituent on the thiophene conjugated side chain of the benzodithiophene (BDT) units for studying effect of the substituents on the photovoltaic performance of the polymers. The alkylthio side chain, red-shifted absorption down-shifted the highest occupied molecular orbital (HOMO) level and improved crystallinity of the 2D conjugated polymers. With linear alkylthio side chain, the tailored polymer J61 exhibits an enhanced J SC of 17.43 mA/cm2, a high V OC of 0.89 V, and a PCE of 9.53% in the best non-fullerene PSCs with the polymer as donor and ITIC as acceptor. To the best of our knowledge, the PCE of 9.53% is one of the highest values reported in literature to date for the non-fullerene PSCs. The results indicate that J61 is a promising medium bandgap polymer donor in non-fullerene PSCs.